2015
DOI: 10.3945/jn.114.207944
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Almonds Increase Serum HDL Cholesterol in Coronary Artery Disease Patients in a Randomized Controlled Trial

Abstract: A low dose of almonds (10 g/d) consumed before breakfast can increase HDL cholesterol, in addition to improving other markers of abnormal lipid metabolism in CAD patients with low initial HDL cholesterol. This trial was registered at the Australian New Zealand Clinical Trial Registry as ACTRN12614000036617.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 53 publications
1
64
1
2
Order By: Relevance
“…These results were different from previous studies that given MSG will increase the body weight and even the risk of metabolic syndrome in the consumption [11]. The different results in this study may be caused by the treatment method of feeding the mice treatment group for the MSG giventhat can induce stress.…”
Section: Resultscontrasting
confidence: 56%
“…These results were different from previous studies that given MSG will increase the body weight and even the risk of metabolic syndrome in the consumption [11]. The different results in this study may be caused by the treatment method of feeding the mice treatment group for the MSG giventhat can induce stress.…”
Section: Resultscontrasting
confidence: 56%
“…lipoprotein was significantly increased in addition to improvement in other lipid parameters after 6 and 12 weeks (Jamshed, Sultan, Iqbal, & Gilani, 2015).…”
Section: Computer-based Photographic Analysis Of Facial Wrinklesmentioning
confidence: 88%
“…In particular, for consumers who value food‐based therapies as nutritional options for antiaging purposes, almond consumption has appeal due to its overall health‐promoting benefits including essential fatty acids and vitamin E. Of particular interest is that almonds have benefits beyond the skin‐related effects noted in this study (Hyson, Schneeman, & Davis, ; Kalita et al, ). For instance, one clinical study demonstrated that in patients with coronary artery disease who consumed a small dose (10 g/day) of almonds that were soaked overnight and taken on an empty stomach, the levels of the protective high‐density lipoprotein was significantly increased in addition to improvement in other lipid parameters after 6 and 12 weeks (Jamshed, Sultan, Iqbal, & Gilani, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, plants have always served as a source of folk medicine and modern drugs to meet health care needs of mankind (Gilani & Atta‐ur‐Rahman, ; Mishra et al, ; Mishra et al, ; Saily, Sabu, Mohan, Gupta, & Sondhi, ; Sharifi‐Rad et al, ). Due to the high cost and safety issues of pharmaceutical medicine, there is renewed interest in the utilization of plants/herbs both as a food and medicine (Anwar et al, ; Jamshed, Sultan, Iqbal, & Gilani, ; Muhammad, Hussain, Anwar, Ashraf, & Gilani, ). The medicinal products obtained from various plants are considered safer (Abbas, Anwar, & Ahmad, ; Ahmad & Sher, ; Ahmed & Gilani, ).…”
Section: Introductionmentioning
confidence: 99%